Penerapan Model Problem Based Learning (PBL) dalam Pembelajaran Tematik Terpadu di Kelas V Sekolah Dasar - Wulandari, Oktavia; Taufina, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to analyze the role of the Problem Based Learning (PBL) model in integrated thematic learning in elementary schools. The model that has been widely adopted to support the learning centered learning model and emphasizes the involvement of students in the active learning process as in the integrated thematic learning process is the Problem Based Learning (PBL) model. In integrated thematic learning students are directed at student-centered learning, students are actively searching, group-based learning, and using real-world problems as a context for students to learn about critical thinking and problem solving skills. This is in line with the Problem Based Learning (PBL) learning model. In this study researchers used a literature study (library research). First the researchers formulated the research problem, then proceeded to search for electronic journals via google schoolar. From the search, 15 relevant journals were analyzed for their role in integrated thematic learning using the Problem Based Learning (PBL) model. The keywords used for journal research are Problem Based Learning, learning outcomes, elementary school. The analysis turned out to show that the Problem Based Learning model was able to improve student learning outcomes starting from the lowest 28% to the highest 93% with an average of 58%.